A numerical study on a photovoltaic thermal system integrated with a thermoelectric generator module. (June 2020) - Salari, Ali; Parcheforosh, Ali; Hakkaki-Fard, Ali; Amadeh, Ali
Abstract: In this work, a three-dimensional numerical model is developed to investigate the performance of a photovoltaic thermal system integrated with a thermoelectric generator module (PVT/TE). Furthermore, the effects of various operating parameters such as solar radiation, coolant mass flow rate, and inlet and ambient temperatures on the performance of both the PVT and PVT/TE systems are investigated and compared. Based on the obtained results, the electrical efficiency of the PVT/TE system, when exposed to solar radiation of 600 and 1000 W/m 2, is 6.23% and 10.41% higher than that of the PVT system, respectively. Besides, the electrical efficiency of the PVT and PVT/TE by increasing the inlet fluid temperature from 26 °C to 34 °C, reduces by 2.58% and 4.56%, respectively. Furthermore, by increasing the ambient temperature from 26 °C to 34 °C, the electrical efficiency of the PVT reduces by 1.43%, the electrical efficiency of the PVT/TE increases by 0.82%. Based on the simulation results, the electrical efficiency of the PVT/TE system is much higher than that of the PVT system, while the PVT system benefits from higher thermal efficiency in comparison to the PVT/TE system. Highlights: A numerical model is developed to investigate the performance of the PVT/TE system. The effects of different parameters on the performance of the system are studied. Performance of a conventional PVT system is compared with that of a PVT/TE system. Electrical efficiency of the PVT/TE system is higher than that of the PVT system.